Source Tracker Modeling Based on 16S rDNA Sequencing and Analysis of Microbial Contamination Sources for Pasteurized Milk - Du, Bingyao; Meng, Lu; Wu, Haoming; Yang, Huaigu; Liu, Huimin; Zheng, Nan; Zhang, Yangdong; Zhao, Shengguo; Wang, Jiaqi (Frontiers in Nutrition, 2022)
Milk is rich in fat, protein, minerals, vitamins, peptides, immunologically active substances and other nutrients, and it plays an important role in satisfying human nutrition and health. However, dairy product safety incidents caused by microbial contamination have occurred. We found that the total bacterial numbers in the final pasteurized product were low and far below the limit requirements of the food safety standards of the European Union, the United States and China. At the genus level, the primary microbial groups found in milk samples were Acinetobacter, Macrococcus, Pseudomonas and Lactococcus, while in the equipment rinse water and air samples there were contamination by Stenotrophomonas and Acinetobacter. The Source Tracker model analysis indicated that the microorganisms in the final milk products were significantly related to the contamination in product tanks and raw milk. Therefore, it is hope that this work can give guidance to pinpoint contamination problems using the proper quality control sampling at specific stages in the pasteurization process.